2013
DOI: 10.1177/1352458513516529
|View full text |Cite
|
Sign up to set email alerts
|

Methylation differences at the HLA-DRB1 locus in CD4+ T-Cells are associated with multiple sclerosis

Abstract: Our findings provide the first evidence for association of DNA methylation at HLA-DRB1 in relation to MS risk. Further studies are now warranted to validate and understand how these findings are involved in MS pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 27 publications
12
110
2
1
Order By: Relevance
“…In this study, we chose to focus on CD4+ T cells as they are thought to be the main cell infiltrates. Our previous studies also show that CD4+ T cells exhibit significant changes in methylation profiles in RRMS [33, 34]. …”
Section: Discussionmentioning
confidence: 66%
“…In this study, we chose to focus on CD4+ T cells as they are thought to be the main cell infiltrates. Our previous studies also show that CD4+ T cells exhibit significant changes in methylation profiles in RRMS [33, 34]. …”
Section: Discussionmentioning
confidence: 66%
“…In patients with multiple sclerosis, HLA transmission was distorted by the parent of origin and by gender of the affected offspring [7]. A differential methylation signal with a peak at HLA-DRB1 was observed in CD4 + T cells of multiple sclerosis patients compared with controls in another study, suggesting a potential explanation for this observation [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Methylation pattern analysis of a CpG island located in the PAD2 promoter showed that over-expression is due to promoter demethylation in PBMCs from patients with MS (Calabrese et al, 2012). Graves and colleagues first reported that differential DNA methylation at HLA-DRB1 is related to MS risk (Graves et al, 2013). In addition, DNA methylation/demethylation also has been identified in PBMCs of MS patients.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 96%